The changing world of work : work-life balance amongst women in leadership at selected South African institutions of higher learning - Maribe, Thakgatso Theresa (My University, 2025)
In the African culture, women’s roles involved raising children, cooking, and cleaning, but today women have changed this and made a mark in the corporate world by occupying leadership positions. However, the world of work is changing, which has brought too many challenges to women in leadership at institutions of higher learning, requiring them to balance their personal and professional lives. This study aimed to explore work-life balance challenges brought about by the changing nature of the world of work among women in leadership at selected institutions of higher learning. The study used an exploratory research design, following a phenomenology research method which falls under a qualitative research approach. Sixteen participants were sampled using the purposive sampling technique, which falls under the non-probability sampling methods. Semi-structured interviews were conducted to collect data from research participants and thematic analysis was used to analyse the data. Six themes emerged from the research findings, namely: Work Interfering with personal life as the main challenge of work-life balance; high expectations from management level; workload from leadership responsibility and supporting structure as the causes of work-life balance challenges; health and wellness issues as the consequences of work-life balance challenges; and lastly work-life integration pathways used by women in leadership as probable solutions to work-life balance challenges. The study recommends that top management to come up with alternatives such as amending policies to accommodate a balanced work-life; attending wellness programs; hiring more assistants; reducing NQF level requirements for leadership positions; having software where employees express their work-life balance; and women in leadership taking ownership of their work-life imbalance by setting boundaries and limitation to time spent on their work.
Thesis (M. COM. (Human Resources Management)) -- University of Limpopo, 2025
Keywords: Institutions of Higher Learning; Leadership; Women in leadership; Work-life balance; Work-life balance; Leadership in women; Education, Higher -- South Africa